2003
DOI: 10.1021/ic025967d
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Anhydrous and Aqua Copper(II) Amino Acid Complexes:  A New Molecular Mechanics Force Field Parametrization Based on Quantum Chemical Studies and Experimental Crystal Data

Abstract: This paper presents the vacuum structures of aquacopper(II) bis(amino acid) complexes with glycine, sarcosine, N,N-dimethylglycine, and N-tert-butyl-N-methylglycine estimated using the B3LYP method. The differences between the B3LYP vacuum structures and experimental crystal structures suggested considerable influence of crystal lattice packing effects on the changes in the complexes' geometries. A previously developed molecular mechanics force field for modeling anhydrous copper(II) amino acidates was reoptim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(119 citation statements)
references
References 55 publications
(165 reference statements)
10
105
1
3
Order By: Relevance
“…A key step was to locate the low-energy conformers for each coordination number (4-6) and cluster size (n ) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] hydrogen bond between water molecules on the periphery of a Cu(II)-water complex is stronger than the energy of water binding to the vacant axial sites on Cu 2+ . This much less favorable interaction of water molecules in the axial directions is due to the double occupation of the Cu 2+ 3d z 2 orbital effectively screening the positive charge on the metal ion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A key step was to locate the low-energy conformers for each coordination number (4-6) and cluster size (n ) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] hydrogen bond between water molecules on the periphery of a Cu(II)-water complex is stronger than the energy of water binding to the vacant axial sites on Cu 2+ . This much less favorable interaction of water molecules in the axial directions is due to the double occupation of the Cu 2+ 3d z 2 orbital effectively screening the positive charge on the metal ion.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Detailed information on ligands arrangement around the Cu(II) ion is only available in the solid state [6][7][8][9][10][11][12][13] whereas the structural information in the aqueous phase [13][14][15][16][17][18][19][20] is less definitive and available only for few Cu 2+ complexes. Although static [20][21][22][23][24][25][26][27][28][29][30] and dynamic [31][32][33][34][35][36][37] electronic structure calculations can, in principle, provide such information, realistic modeling of Cu(II) complexes in aqueous solution with highly flexible coordination environment still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We checked the accuracy of the pseudopotential treatment of Cu by comparing with the all-electron calculations employing the TZVP basis set and the diffuse function (R d ) 0.07) on Cu. 16 ] showed that the use of the ECP approximation leads to only small changes in bond lengths (root mean squared deviation of 0.004 and 0.070 Å for equatorial and axial bonds, respectively) and relative energies (0.06-0.26 kcal/mol) without affecting the metal coordination structure. The overall good agreement thus justifies the subsequent use of the LACV3P ECP for Cu.…”
Section: 42mentioning
confidence: 99%
“…Distortion of the octahedral geometry occurs along one of the three 4-fold axes. One of the important consequences of the Jahn-Teller effect is a variability of the coordination geometry of Cu 2+ in the solid state [14][15][16][17][18][19][20][21] and the fast first-shell ligand exchange dynamics in the aqueous phase. 22,23 Surprisingly, the coordination environment even for the simplest hydrated Cu(II) ion has been the subject of extensive debate in recent years.…”
Section: Introductionmentioning
confidence: 99%